2022
DOI: 10.3389/fcvm.2022.1041852
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and long-term outcomes of heart block after transcatheter device closure of perimembranous ventricular septal defect

Abstract: BackgroundHeart block is the most common and concerning complication associated with transcatheter device closure of perimembranous ventricular septal defect (pmVSD) and its occurrence remains a great challenge for device closure.MethodsBetween June 2002 and June 2020, 1076 pediatric patients with pmVSD, who successfully underwent transcatheter device closure in our center, were enrolled in this cohort study, with a median follow-up of 64 months (range: 1 to 19 years).ResultsOf 1076 patients, 234 (21.8%) devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
0
Order By: Relevance
“…Regarding VSD type, our data was consistent with almost all the previously published studies [28][29][30]. Device size as an independent predictor of postprocedural CHB was additionally verified by a similar multivariate logistic regression evaluation that was conducted by Jiang et al [31]. However, the latter study also illustrated that type of the device, particularly the thin waist occlude, was a stand-alone risk factor for the development of postoperative heart block.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding VSD type, our data was consistent with almost all the previously published studies [28][29][30]. Device size as an independent predictor of postprocedural CHB was additionally verified by a similar multivariate logistic regression evaluation that was conducted by Jiang et al [31]. However, the latter study also illustrated that type of the device, particularly the thin waist occlude, was a stand-alone risk factor for the development of postoperative heart block.…”
Section: Discussionsupporting
confidence: 90%
“…This was not significantly higher compared to the incidence ranging from 21.8% to 35.7% from the studies that meticulously identified all post-procedural arrhythmias. [28][29][30] Left anterior hemiblock was the most common abnormality similar to the experience from other studies. [31] As the surgical anatomy identified the conduction system to be closer to the LV side of the defect than the RV side, a transvenous antegrade cannulation from the RV end might not increase the possibility of post-procedural complications.…”
Section: Impact On Atrioventricular Conduction Systemsupporting
confidence: 80%